Patent foramen ovale closure vs. medical therapy for cryptogenic stroke: a meta-analysis of randomized controlled trials. (24th March 2018) - Ahmad, Yousif; Howard, James P; Arnold, Ahran; Shin, Matthew Shun; Cook, Christopher; Petraco, Ricardo; Demir, Ozan; Williams, Luke; Iglesias, Juan F; Sutaria, Nilesh; Malik, Iqbal; Davies, Justin; et al.
Abstract: Aims: The efficacy of patent foramen ovale (PFO) closure for cryptogenic stroke has been controversial. We undertook a meta-analysis of randomized controlled trials (RCTs) comparing device closure with medical therapy to prevent recurrent stroke for patients with PFO. Methods and results: We systematically identified all RCTs comparing device closure to medical therapy for cryptogenic stroke in patients with PFO. The primary efficacy endpoint was recurrent stroke, analysed on an intention-to-treat basis. The primary safety endpoint was new onset atrial fibrillation (AF). Five studies (3440 patients) were included. In all, 1829 patients were randomized to device closure and 1611 to medical therapy. Across all patients, PFO closure was superior to medical therapy for prevention of stroke [hazard ratio (HR) 0.32, 95% confidence interval (95% CI) 0.13–0.82; P = 0.018, I 2 = 73.4%]. The risk of AF was significantly increased with device closure [risk ratio (RR) 4.68, 95% CI 2.19–10.00, P <0.001, heterogeneity I 2 = 27.5%)]. In patients with large shunts, PFO closure was associated with a significant reduction in stroke (HR 0.33, 95% CI 0.16–0.72; P = 0.005), whilst there was no significant reduction in stroke in patients with a small shunt (HR 0.90, 95% CI 0.50–1.60; P = 0.712). There was no effect from the presence or absence of an atrial septal aneurysm on outcomes ( P = 0.994). Conclusion: In selected patients with cryptogenic stroke, PFO closure is superior to medical therapy for the prevention of further stroke: this is particularly true for patients with moderate-to-large shunts. Guidelines should be updated to reflect this.